Engaged approaches to deliberative civic learning: case study of a small urban middle school - Kakim, Saya (Kansas State University, 2022)
Given the current context of high political polarization and democratic backsliding, the importance of developing the capacity of youth to participate in civic life so they can engage respectfully with one another is crucial. This study considers deliberative civic learning as a pathway for youth capacity building for democratic citizenship and draws upon deliberative pedagogy. In addition, the search for innovative pathways to high-quality deliberative civic learning calls for collaborative programmatic efforts and community-university partnerships. This study considers a partnership between a Midwestern land-grant institution, cooperative extension, youth development program, a non-partisan organization for deliberation and dialogue, and a public middle school. In this respect, this study also draws on engaged approaches to research that have practical and ethical implications. By utilizing a descriptive, interpretive single case study design, this exploratory multidisciplinary study aimed to describe gifted middle school students’ learning experiences in visual thinking strategies (VTS) integrated with National Issues Forums (NIF). To accomplish this, the study addressed the following research questions: What do gifted middle school students learn as they engage in deliberative civic learning through participation in VTS integrated with NIF? a) How do gifted middle school students describe their experience in VTS integrated with NIF? b) What are the perceived outcomes of gifted middle school students’ participation in VTS integrated with NIF? The data was collected using various methods such as non-participant observation, interview, questionnaire, focus group, curriculum and artifact analysis, field notes, and forum transcripts. The data analysis was conducted by applying an iterative approach to coding, employing thematic analysis, and using a macro-analytic approach to qualitative content analysis. The findings suggest that the engaged efforts ensured meaningful student engagement with deliberative civic learning and led to students’ development and growth across the different levels of participation. The results reveal that the gifted early adolescents were able to practice active listening skills to acquire a better understanding of their peers’ viewpoints and consider options that benefit the community based on new information and reflection of a variety of perspectives. The findings also suggest that deliberative civic learning provided the gifted middle school students with an opportunity to learn about their peers’ experiences and leadership development. The research participants associated their greater awareness of the various opinions of their peers and willingness to learn about others’ perspectives with the learning experience in VTS integrated with NIF. The study’s findings are consistent with the existing deliberative pedagogy literature. This dissertation project contributes to a larger body of scholarship regarding capacity building of gifted early adolescents for democratic citizenship. The research has practical implications for K-12 educators, school districts administration, and youth development programs.
Keywords: Engaged scholarship; Deliberative pedagogy; Middle school; Deliberative civic learning; Visual thinking strategies; Leadership development